Analysis of Local Government Financial Ratios and Their Impact on Capital Expenditures for Economic Growth in East Java Province - Akromul Khaidar (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the effect of regional financial ratios on capital expenditure and their implications for economic growth in East Java Province. The financial ratios examined include the independence ratio, effectiveness ratio, and efficiency ratio as indicators of local government financial performance. Capital expenditure is positioned as an intervening variable that plays a role in supporting infrastructure development and productive sectors. This research employs a quantitative approach using data analysis from regional government financial reports. The results indicate that the regional independence ratio has a positive effect on capital expenditure, which in turn contributes to economic growth. Meanwhile, the effectiveness and efficiency of regional financial management also play a significant role in optimizing the allocation of development budgets.